The Second Volume of Pierson's Principles of Economics - Seager, Henry R.; Pierson, N. G. (Quarterly Journal of Economics, 1913)
Journal Article The Second Volume of Pierson's Principles of Economics Get access Henry R. Seager Henry R. Seager Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 27, Issue 4, August 1913, Pages 651–655, https://doi.org/10.2307/1883446 Published: 01 August 1913